Natural Compounds as Medical Strategies in the Prevention and Treatment of Psychiatric Disorders Seen in Neurological Diseases - Küpeli Akkol, Esra; Tatlı Çankaya, Irem; Şeker Karatoprak, Gökçe; Carpar, Elif; Sobarzo-Sánchez, Eduardo; Capasso, Raffaele (Frontiers in Pharmacology, 2021)
Psychiatric disorders are frequently encountered in many neurological disorders, for instance, Alzheimer’s and Parkinson diseases along with epilepsy, migraine, essential tremors, and stroke. The most common comorbid diagnoses in neurological diseases are depression and anxiety disorders along with cognitive impairment. Whether the underlying reason is due to common neurochemical mechanisms or loss of previous functioning level, comorbidities are often overlooked. Various treatment options are available, such as pharmacological treatments, cognitive-behavioral therapy, somatic interventions, or electroconvulsive therapy. However oral antidepressant therapy may have some disadvantages, such as interaction with other medications, low tolerability due to side effects, and low efficiency. Natural compounds of plant origin are extensively researched to find a better and safer alternative treatment. Experimental studies have shown that phytochemicals such as alkaloids, terpenes, flavonoids, phenolic acids as well as lipids have significant potential in in vitro and in vivo models of psychiatric disorders. In this review, various efficacy of natural products in in vitro and in vivo studies on neuroprotective and their roles in psychiatric disorders are examined and their neuro-therapeutic potentials are shed light.